Toward New Sources of Competitiveness in Bangladesh : Key Insights of the Diagnostic Trade Integration Study - Kathuria, Sanjay; Malouche, Mariem Mezghenni (Washington, DC: World Bank, 2015)
The Diagnostic Trade Integration Study identifies the following actions centered around four pillars to sustain and accelerate export growth: (1) breaking into new markets through a) better trade logistics to reduce delivery lags; as world markets become more competitive and newer products demand shorter lead times, to generate new sources of competitiveness and thereby enable market diversification; and b) better exploitation of regional trading opportunities in nearby growing and dynamic markets, especially East and South Asia; (2) breaking into new products through a) more neutral and rational trade policy and taxation and bonded warehouse schemes; b) concerted efforts to spur domestic investment and attract foreign direct investment, to contribute to export promotion and diversification, including by easing the energy and land constraints; and c) strategic development and promotion of services trade; (3) improving worker and consumer welfare by a) improving skills and literacy; b) implementing labor and work safety guidelines; and c) making safety nets more effective in dealing with trade shocks; and (4) building a supportive environment, including a) sustaining sound macroeconomic fundamentals; and b) strengthening the institutional capacity for strategic policy making aimed at the objective of international competitiveness to help bring focus and coherence to the government's reform efforts.